Clinical Utility of an Enzyme-Linked Immunosorbent Assay for Detecting Anti-Melanoma Differentiation-Associated Gene 5 Autoantibodies - Sato, Shinji; Murakami, Akihiro; Kuwajima, Akiko; Takehara, Kazuhiko; Mimori, Tsuneyo; Kawakami, Atsushi; Mishima, Michiaki; Suda, Takafumi; Seishima, Mariko; Fujimoto, Manabu; Kuwana, Masataka (PLOS ONE, 2016)
Objective Autoantibodies to melanoma differentiation-associated gene 5 (MDA5) are specifically expressed in patients with dermatomyositis (DM) and are associated with a subset of DM patients with rapidly progressive interstitial lung disease (RP-ILD). Here, we examined the clinical utility of a newly developed enzyme-linked immunosorbent assay (ELISA) system for detecting these antibodies. Methods Here we developed an improved ELISA for detecting anti-MDA5 antibodies. We then performed a multicenter clinical study involving 8 medical centers and enrolled 242 adult patients with polymyositis (PM)/DM, 190 with non-PM/DM connective tissue disease (CTD), 154 with idiopathic interstitial pneumonia (IIP), and 123 healthy controls. Anti-MDA5 antibodies in the patients’ serum samples were quantified using our newly developed ELISA, and the results were compared to those obtained using the gold-standard immunoprecipitation (IP) assay. In addition, correlations between the ELISA-quantified anti-MDA5 antibodies and clinical characteristics were evaluated. Results In patients with PM/DM, the anti-MDA5 antibody measurements obtained from the ELISA and IP assay were highly concordant; the ELISA exhibited an analytical sensitivity of 98.2%, specificity of 100%, positive predictive value of 100%, and negative predictive value of 99.5% (compared to the IP assay). Anti-MDA5 antibodies were detected in 22.7% of the DM patients, but not in any of the patients with PM, non-PM/DM CTD, or IIP. Clinically amyopathic DM, RP-ILD, arthritis, and fever were more prevalent in DM patients who were anti-MDA5 antibody-positive than in those who were antibody-negative (P ≤ 0.0002 for all comparisons). In addition, anti-MDA5 antibody-positive patients with RP-ILD exhibited higher antibody levels than those without RP-ILD (P = 0.006). Conclusion Our newly developed ELISA can detect anti-MDA5 antibodies as efficiently as the gold standard IP assay and has the potential to facilitate the routine clinical measurement of anti-MDA5 antibodies in patients who suspected to have DM.